2022
DOI: 10.1109/access.2022.3204028
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Electrical, Thermal, and Mechanical Properties of Silicone Rubber ATH Nanocomposites

Abstract: In the present study, investigations have been carried out by choosing the nano-sized ATH (30 -50 nm) particles as filler content in silicone rubber to acquire a deep insight to understand the use of nano ATH fillers in silicone rubber on its performance, to use it as insulation structure as an outdoor insulator. Variation in the surface condition of silicone rubber nanocomposites due to corona aging and the recovery characteristics analysis carried out through contact angle measurement. Nano ATH added in sili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…A pulse energy of 30 mJ of 200 pulses is applied at the front side of the samples, which produces molecular vibration and breaks the atomic bonds of the epoxy‐based sample. This generates heat and is captured from the rear side of the sample using a handheld forward looking infrared (FLIR) camera 14 . The dimensions of the samples are 30 × 30 mm 2 .…”
Section: Experimental Studymentioning
confidence: 99%
See 1 more Smart Citation
“…A pulse energy of 30 mJ of 200 pulses is applied at the front side of the samples, which produces molecular vibration and breaks the atomic bonds of the epoxy‐based sample. This generates heat and is captured from the rear side of the sample using a handheld forward looking infrared (FLIR) camera 14 . The dimensions of the samples are 30 × 30 mm 2 .…”
Section: Experimental Studymentioning
confidence: 99%
“…This generates heat and is captured from the rear side of the sample using a handheld forward looking infrared (FLIR) camera. 14 The dimensions of the samples are 30 Â 30 mm 2 . Additionally, a laser flash analysis test is performed to determine the thermal conductivity of the fabricated samples.…”
Section: Thermal Imaging With Flirmentioning
confidence: 99%
“…The experimental setup for measuring water droplet initiated corona inception voltage is shown in Fig 1 . It includes a signal generator (Tektronix 3051C), a high voltage amplifier (Trek type 20/20 C), and stainless-steel electrodes with a 45 • cut at the tip, as per IEC 60112. The complete procedure for measuring for CIV is explained in the previous study [35].…”
Section: Water Droplet Initiated Corona Inception Studiesmentioning
confidence: 99%
“…Their research revealed that the introduction of nanosized ATH improved the interface region between the matrix and the filler. This interface region provided a free pathway for charge carriers to transport into the material's interior [7]. Z. P. Yan et al applied both nano and micron-sized SiO2 coatings to the surface of silicone rubber, resulting in silicone rubber composites with superhydrophobic properties.…”
Section: Introductionmentioning
confidence: 99%